Chlorophyll-a and phytoplankton community responses to cyclone Dana in the coastal waters of the north-western Bay of Bengal - Amit Kumar Jena; Kamal Kumar Barik; Sumit Kumar Mohanty; Suchismita Sahu; Suchismita Srichandan; Sanjiba Kumar Baliarsingh; Alakes Samanta; Pratap Kumar Chhotaray; Sudheer Joseph; T. M. Balakrishnan Nair (Spatial Information Research, 2026)

Hydrochemical budgeting of a tropical estuary Vis-à-Vis tidal dynamics: Ecosystem trophic status assessment - Susmita Raulo; Sanjiba Kumar Baliarsingh; Alakes Samanta; Aneesh A. Lotliker; Sudheer Joseph; Sambit Singh; Tamoghna Acharyya; Vikrant V. Patil; T.M. Balakrishnan Nair (Journal of Marine Systems, 2026)

Backtracking the Origins of a Jellyfish Beach Stranding Event Following Cyclone Mocha - Chennuri Sathish; Amit Kumar Jena; Sanjiba Kumar Baliarsingh; Alakes Samanta; Rajesh Kumar Pradhan; Biraja Kumar Sahu; Sudheer Joseph; T. M. Balakrishnan Nair (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Probing Indian Oil Sardine Aggregation Events Along the West Coast of India - Bhagyashree Dash; Dhanya M. Lal; Sanjiba Kumar Baliarsingh; Alakes Samanta; Sudheer Joseph; T. M. Balakrishnan Nair (Journal of the Indian Society of Remote Sensing, 2026)

Marine carbon dioxide removal (mCDR) in the Indian seas: current understanding, regional opportunities, and future directions - Sumit S. Sonar; Susmita Raulo; Suchismita Srichandan; Dhanya M. Lal; Sanjiba K. Baliarsingh; Alakes Samanta; Sudheer Joseph; T.M. Balakrishnan Nair (Mitigation and Adaptation Strategies for Global Change, 2026)

Long-term variability of chlorophyll- a in the north-western Bay of Bengal: linking phytoplankton size class and diatom dynamics - Suchismita Srichandan; Amit Kumar Jena; Alakes Samanta; Susmita Raulo; V. V. S. S. Sarma; Sanjiba Kumar Baliarsingh; Amit Maharana; Kamal Kumar Barik (International Journal of Remote Sensing, 2026)

Regional chlorophyll- a retrieval algorithm for Indian coastal waters using optical classification and band optimization - Alakes Samanta; Sanjiba Kumar Baliarsingh; Aneesh A. Lotliker (International Journal of Remote Sensing, 2026)

Satellite retrieval of phytoplankton size class biomass: algorithm evaluation and long-term patterns in the northern Arabian Sea - Sanjiba Kumar Baliarsingh; Alakes Samanta; P. Minu; S. Ayana; Aneesh A. Lotliker (International Journal of Remote Sensing, 2026)

Short‐Term Prediction of Hilsa ( Tenualosa ilisha ) Catch in the Northern Bay of Bengal Using Advanced Machine Learning Algorithms - Sandip Giri; A. P. Joshi; Prasanna Kanti Ghoshal; Sudheer Joseph; Kunal Chakraborty; Alakes Samanta; T. M. Balakrishnan Nair; T. Srinivasa Kumar (Fisheries Oceanography, 2025)
Hilsa is a vital transboundary fishery resource in the Bay of Bengal (BoB), holding commercial, ecological, and cultural importance. This study aims to develop a short‐term prediction of Hilsa catch in the northern BoB using a machine learning (ML) model. The prediction technique was developed considering the georeferenced Hilsa catch per unit effort (CPUE) as a function of environmental variables like surface salinity, sea surface temperature (SST), surface current speed, and direction. We employed two advanced ML algorithms, viz., random forest (RF) and 5. (XGBoost) to examine their efficacy in the short‐term prediction of Hilsa for the northern BoB and compared the model performance with a baseline information obtained through multiple linear regression (MLR). Our analysis showed significant improvement in the prediction accuracy using advanced ML techniques where XGBoost again outperformed RF. The root mean square error (RMSE) values between observed and predicted CPUE for RF and XGBoost models were 5.72 and 5.63 kg/h, respectively. The correlation coefficient (r) between the observed and predicted catch were 0.90 and 0.93 for RF and XGBoost, respectively. SHapley Additive exPlanations (SHAP) analysis revealed the highest influence (58.38%) of surface current speed on the Hilsa CPUE. We generated the spatial prediction maps of Hilsa CPUE using the best performing (XGBoost) model with 85% prediction efficiency. This study showed the potential of the XGBoost model in developing a short‐term prediction for Hilsa in the northern BoB, towards developing Hilsa fishery advisory for sustainable management of these fishery resources.

Probing a Blue Button Jellies Beach Stranding Event on the East Coast of India - Kamal Kumar Barik; Amit Kumar Jena; Sumit Kumar Mohanty; Suchismita Srichandan; Sanjiba Kumar Baliarsingh; Alakes Samanta; Pratap K. Chhotaray; Sudheer Joseph; T. M. Balakrishnan Nair (Journal of the Indian Society of Remote Sensing, 2025)

Environmental controls on chlorophyll-a and dissolved oxygen variability in contrasting Basins of the Northern Indian ocean - Kunal Chakraborty; Linta Rose; B. Rohith; Sanjiba Kumar Baliarsingh; Alakes Samanta (Marine Environmental Research, 2025)

Monsoonal influence on floating marine litter pathways in the Bay of Bengal - Lianne C. Harrison; Jennifer A. Graham; Piyali Chowdhury; Tiago A. M. Silva; Danja P. Hoehn; Alakes Samanta; Kunal Chakraborty; Sudheer Joseph; T. M. Balakrishnan Nair; T. Srinivasa Kumar (Ocean Science, 2025)
Marine litter in the Bay of Bengal has been under-studied despite large quantities of mismanaged waste reportedly entering the ocean from its surrounding countries. The seasonal reversal of monsoon currents in this region provides a unique environment for the transport of floating macro-litter. A particle tracking model is used here to investigate source-to-sink connectivity of marine debris between countries via oceanic pathways in the Bay of Bengal. We use an approach considering uniform release of particles along the entire coastline, avoiding the considerable uncertainties associated with assumed riverine sources. Two different simulations are considered, forced with either a high-resolution ocean hindcast developed specifically for the Bay of Bengal or a lower-resolution dataset which includes data assimilation. The vast majority of particles released during our simulations were found to beach within 16 months; most particles beached in their country of origin (57 %–90 %), with connectivity towards Myanmar accounting for the second highest connectivity rates (2 %–29 %) from many countries within the Bay of Bengal. This is likely due to the relatively large size of Myanmar's coastline and that it lies in the path of the East India Coastal Current for much of the year (February–September). Patterns of connectivity were found to change along with the monsoon and the post-monsoon period (October–January) showed a notably greater dispersal of particles than the rest of the year. Both simulations were evaluated using the pathways of undrogued surface drifters, which moved primarily within the open ocean, with better agreement found here for particles advected by data-assimilated ocean velocities. This study will therefore crucially inform future research and policy in this region, providing advice on the benefits and suitability of selecting different modelling approaches independent of assumptions of the source locations or volumes.

Validation and assessment of Potential Fishing Zone (PFZ) dynamics along the southwest coast of India through environmental proxies and trophic guild analysis - Dhanya Mohan Lal; Harisha; Alakes Samanta; Sudheer Joseph; S Suresh Kumar; Sanjiba Kumar Baliarsingh; T M Balakrishnan Nair (Environmental Impact Assessment Review, 2025)

Corrigendum to article “Determining chlorophyll-a thresholds for characterizing algal bloom conditions: An ocean colour remote sensing approach” [Sci. Total Environ. 961 (2025) 178353] - Susmita Raulo; Alakes Samanta; Sanjiba Kumar Baliarsingh; V.V.S.S. Sarma; Sudheer Joseph; T.M. Balakrishnan Nair; Suchismita Srichandan (Science of The Total Environment, 2025)

Linking a Tropical Cyclone and Ocean Conditions to Jellyfish Stranding Event on the Indian East Coast - Amit Kumar Jena; Manasa Ranjan Behera; Suchismita Srichandan; Sanjiba Kumar Baliarsingh; Sachiko Mohanty; Alakes Samanta; V. K. Srineash (Thalassas: An International Journal of Marine Sciences, 2025)

Determining chlorophyll-a thresholds for characterizing algal bloom conditions: An ocean colour remote sensing approach - Susmita Raulo; Alakes Samanta; Sanjiba Kumar Baliarsingh; V.V.S.S. Sarma; Sudheer Joseph; T.M. Balakrishnan Nair; Suchismita Srichandan (Science of The Total Environment, 2025)

Evolution and recent trends of Indian oil sardine research: A review - Bhagyashree Dash; Sanjiba Kumar Baliarsingh; Alakes Samanta; Sidhartha Sahoo; Sudheer Joseph; T.M. Balakrishnan Nair (Ocean & Coastal Management, 2024)

Investigating Indian oil sardine aggregation events in coastal waters of the southeastern Arabian sea - Sanjiba Kumar Baliarsingh; Bhagyashree Dash; Amit Kumar Jena; Susmita Raulo; Alakes Samanta; Sudheer Joseph; Thayannur Mullachery Balakrishnan Nair; Suchismita Srichandan; Sivanpillai Sureshkumar (Environmental Science and Pollution Research, 2024)

An integrated buoy-satellite based coastal water quality nowcasting system: India's pioneering efforts towards addressing UN ocean decade challenges - T.M. Balakrishnan Nair; V.V.S.S. Sarma; Aneesh A. Lotliker; K.R. Muraleedharan; Alakes Samanta; Sanjiba Kumar Baliarsingh; S. Shivaprasad; T.R. Gireeshkumar; Susmita Raulo; S.P. Vighneshwar; R Venkat Shesu; Murali Krishna; et al. (Journal of Environmental Management, 2024)

Sea Surface Temperature and Phytoplankton Abundance as Crucial Proxies for Green Noctiluca Bloom Monitoring in the Northeastern Arabian Sea: A Case Study - Nittala S. Sarma; Sanjiba Kumar Baliarsingh; Aneesh Anandrao Lotliker; Sudarsana Rao Pandi; Alakes Samanta; Suchismita Srichandan (Ocean Science Journal, 2023)

Satellite-Based Characterization of Phytoplankton Blooms in Coastal Waters of the Northwestern Bay of Bengal - Suchismita Srichandan; Sanjiba K. Baliarsingh; Alakes Samanta; Amit K. Jena; Aneesh Anandrao Lotliker; T. M. Balakrishnan Nair; Kamal K. Barik; Tamoghna Acharyya (Journal of the Indian Society of Remote Sensing, 2022)

Deciphering long-term seasonal and tidal water quality trends in the Mahanadi estuary - Tamoghna Acharyya; Bikram Prativa Sudatta; Suchismita Srichandan; Sanjiba Kumar Baliarsingh; Aneesh Anandrao Lotliker; Susmita Raulo; Sambit Singh; Alakes Samanta (Journal of Coastal Conservation, 2021)

Did the Coronavirus Disease 2019 Lockdown Phase Influence Coastal Water Quality Parameters off Major Indian Cities and River Basins? - Aneesh Anandrao Lotliker; Sanjiba Kumar Baliarsingh; R. Venkat Shesu; Alakes Samanta; R. Chandrasekhar Naik; T. M. Balakrishnan Nair (Frontiers in Marine Science, 2021)
The end of the current decade experienced an outbreak of a new strain of coronavirus classified as severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) [coronavirus disease 2019 (COVID-19)] that spread across the globe within a short span of time and was declared as a global pandemic by the World Health Organization. In order to contain the spread of COVID-19, the Indian Government imposed lockdown in various phases, namely, the strict lockdown period (SLP) and relaxed lockdown period (RLP). The present study addresses changes in the magnitude of satellite-derived water quality parameters in the coastal waters off major Indian cities (Mumbai and Chennai) and river basins (Narmada, Mandovi-Zuari, Netravathi, Periyar, Kaveri, Krishna-Godavari, Mahanadi, and Hooghly) along the eastern Arabian Sea (EAS) and western Bay of Bengal (WBoB) during SLP and RLP. The daily climatology (2003–2019) and anomaly (2020) of different water quality parameters, viz ., chlorophyll- a (chl- a ), downwelling diffused attenuation coefficient (k d 490), and particulate organic carbon (POC) were used in the present study to eliminate seasonal biases and to unravel the signature of lockdown-induced changes in the magnitude of the above water quality parameters. During the total lockdown period, the magnitude of the above parameters reduced significantly in the coastal waters of both the EAS and the WBoB. However, this reduction was more significant in the coastal waters of the WBoB, attributed to a reduction in the supply of anthropogenic nutrients. Among different studied locations, the magnitude of water quality parameters significantly decreased off Chennai and Hooghly, during SLP, which subsequently increased during RLP probably due to reduction in anthropogenic material influx during SLP and increase during RLP. During RLP, the coastal waters off Mahanadi showed a maximum decrease in the magnitude of water quality parameters followed by Mandovi-Zuari, irrespective of these regions’ quantum of anthropogenic material input, possibly due to the higher response time of the ecosystem to reflect the reduction in anthropogenic perturbations. The satellite-retrieved water quality parameters have provided valuable insight to efficiently describe the changes in the health of the Indian coastal environment in terms of phytoplankton biomass and water clarity.

Satellite Retrieved Spatio-temporal Variability of Phytoplankton Size Classes in the Arabian Sea - Kamal Kumar Barik; Sanjiba Kumar Baliarsingh; Amit Kumar Jena; Suchismita Srichandan; Alakes Samanta; Aneesh Anandrao Lotliker (Journal of the Indian Society of Remote Sensing, 2020)

Growth and Decay of High-Biomass Algal Bloom in the Northern Arabian Sea - Aneesh A. Lotliker; Sanjiba Kumar Baliarsingh; Alakes Samanta; V. Varaprasad (Journal of the Indian Society of Remote Sensing, 2020)

An Ephemeral Dinoflagellate Bloom during Summer Season in Nearshore Water of Puri, East Coast of India - Sanjiba Kumar Baliarsingh; Rashmin Dwivedi; Aneesh A. Lotliker; Reeta Jayashankar; Biraja Kumar Sahu; Suchismita Srichandan; Alakes Samanta; Chandanlal Parida; Tummala Srinivasakumar; Kali Charan Sahu (Ocean Science Journal, 2018)